Intersection of stunting, animal cohabitation, and the gut microbiota - Rogalin, Henry. (2018)
Abstract: Stunting affects 171 million children worldwide. Risk factors can vary by country but include inadequate nutrition and frequent infections. Stunted children have a higher risk for infections and malabsorption, resulting in a cycle of malnutrition. Several studies have found that the composition of intestinal bacteria, the gut microbiota, is different between children with stunting versus those without stunting. Cohabitation with production animals has been linked to decreased sanitary conditions and increased infections. The rate of stunting in Guatemala is one of the highest in the world at 48% of children under 5 years old. The causes of stunting in this region are poorly understood. We conducted a pilot cross-sectional study using questionnaires, anthropometric measures, and stool samples to explore possible correlates of stunting in a sample of 24-month-old children from the suburban municipality of La Esperanza, Guatemala. Fifty-six children were recruited, and the mothers interviewed. Half of the children in the study were stunted. Animal cohabitation was reported evenly between those with and without stunting. Members of the Lachnospiraceae family were found to be differentially abundant between stunted and non-stunted children. Markers of intestinal inflammation were measured by ELISA, but not found to be associated with height-for-age Z-scores. This preliminary work lays the foundation for further investigations into stunting and the gut microbiota in Guatemala.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: Christine Wanke.; Committee: Honorine Ward, and Robin Ruthazer.; Keyword: Translation studies.